The effect of score types on total score in trampoline gymnastics: Example of the European Championship in Sochi 2021 - Kosova, S.; Koca Kosova, M. (Pedagogy of Physical Culture and Sports, 2021)
Background and Study Aim. Trampoline gymnastics has a versatile scoring system that has evolved and become more complex over the years. This study aimed to find the effect of the difficulty (D), execution (E), time of flight (TOF), and horizontal displacement (HD) scores on the total score in male and female trampoline gymnasts. Material and Methods. The results of the first round in the qualification round in the individual senior category of the 27th European Championships in Trampoline Gymnastics were used for evaluation. Multiple regression analysis (the enter method) was performed to build a model between the total score and D, E, TOF, and HD scores. Results. According to multiple regression analyses, respectively E, TOF, D, and HD scores were predictors of the total score in the men`s first routine, and D, E, TOF, and HD in the men`s second routine (p<0.05). Although women have the same ranking as the men of the second routines, respectively E, D, TOF, and HD scores were predictors of the first routine (p<0.05). Conclusions. The results show that the E score is critical for the first routines and the D score is critical for the second routines. The fact that the first and second routines were constructed with different strategies as per the competition rules may have caused this result. By reminding coaches and athletes of the fact that the types of scores can affect each other, it can be suggested that they adjust their target scores according to the type of routine and the stage and type of competition.